1977
DOI: 10.1128/iai.16.1.88-92.1977
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprophylaxis of experimental Mycoplasma pneumoniae disease: effect of route of administration on the immunogenicity and protective effect of inactivated M. pneumoniae vaccine

Abstract: Formalin-inactivated Mycoplasma pneumoniae vaccine was administered subcutaneously or intranasally to hamsters to examine the effect of route of administration on immunogenicity and protective effect. Parenterally administered vaccine in the doses employed induced serum complement-fixing antibody formation, but did not significantly decrease the frequency of pneumonia following challenge with virulent M. pneumoniae. Intranasally instilled vaccine was ineffective in stimulating serum antibody, but did diminish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…The effective resistance to reinfection provided by prior intratracheal infection of hamsters with virulent M. pneumo-niae ( Fig. 1) supports the findings of previous reports showing resistance of hamsters to reinfection after intranasal or aerosol inoculation with a variety of M. pneumoniae strains (18,19,22,23). Interestingly, the titers of MI antibodies to M. pneumoniae in resistant hamster sera after reinfection was generally no higher (mean titer, 1:22) than those of nonprotected animals that received single or multiple doses of inactivated vaccines.…”
Section: Discussionsupporting
confidence: 87%
“…The effective resistance to reinfection provided by prior intratracheal infection of hamsters with virulent M. pneumo-niae ( Fig. 1) supports the findings of previous reports showing resistance of hamsters to reinfection after intranasal or aerosol inoculation with a variety of M. pneumoniae strains (18,19,22,23). Interestingly, the titers of MI antibodies to M. pneumoniae in resistant hamster sera after reinfection was generally no higher (mean titer, 1:22) than those of nonprotected animals that received single or multiple doses of inactivated vaccines.…”
Section: Discussionsupporting
confidence: 87%
“…Hamsters with a high serum antibody level produced by parenteral administration of killed M. pneumoniae vaccine did not show resistance to the experimental inoculation of M. pneumoniae (5), while animals previously infected with the organisms had a low serum antibody level but were resistant to reinfection (5)(6)(7). Hence those authors concluded that there was little correlation between serum antibody titer and protection against M. pneumoniae pneumonia in vaccinated hamsters.…”
Section: Discussionmentioning
confidence: 99%
“…hamsters previously infected with M. pneumoniae were found to be more resistant to pneumonia upon reinfection, even if they had low serum antibody titers (10,12,16). However, in our previous investigations, resistance to M. pneumoniae infection in hamsters corresponded to serum antibody titers in animals actively immunized with adjuvant vaccine (17) or adoptively immunized with serum preparations (17,18).…”
mentioning
confidence: 70%
“…Hamsters previously infected with M. pneumoniae have been shown to have a low level of serum antibody while resistant to reinfection (10,12,16). Conversely, high-titer serum antibody induced by parenteral administration of killed M. pneumoniae rendered almost no protection in hamsters (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation